Antrodia salmonea Extracts Regulate p53-AR Signaling and Apoptosis in Human Prostate Cancer LNCaP Cells. (29th November 2022) - Chen, Chieh-Yin; Li, Yu-Hsuan; Liao, Wan-Ling; Oner, Muhammet; Cheng, Yu-Chiao; Liu, Fang-Ling; Cheng, Pang-Ting; Celik, Ayse; Wu, Jyh-Horng; Lai, Chih-Ho; Hsieh, Jer-Tsong; Lin, Ho; et al.
Abstract : Antrodia salmonea (AS) is a genus of Antrodia, an epiphyte of Cunninghamia konishii in Taiwan. AS has been reported to have potential therapeutic effects on different diseases, including diarrhea, abdominal pain, and hypertension. AS has been reported to have anticancer effects on numerous cancer types, such as ovarian carcinoma and triple-negative breast cancer. Our previous studies demonstrated that antrocins and triterpenoids are possibly bioactive compositions. However, the effects of AS on prostate cancer remain unknown. Therefore, we investigated the role of AS in prostate cancer growth, apoptosis, and cell cycle regulation. The results showed that AS extracts significantly inhibited the proliferation of prostate cancer LNCaP cells in a dose-dependent manner and increased the levels of apoptotic markers (cleaved PARP and cleaved caspase 3/8/9). In addition, the cell cycle-related proteins CDK1, CDK2, CDK4, and their respective specific regulators Cyclin B1, Cyclin A, and Cyclin D were also affected. Besides, AS treatment increased p53 protein levels and slowed its degradation in LNCaP cells. Interestingly, we found that AS treatment reduced both total protein and Ser-81 phosphorylation levels of the androgen receptor (AR). Notably, the increase of nuclear p53 was accompanied by the down-regulation of AR, suggesting a reverse regulation between p53 and AR in LNCaP cells was triggered by AS treatment. These findings suggest that AS extracts trigger the apoptosis of prostate cancer cells through the reverse regulation of p53 and AR and elucidate that AS extracts might be a potential treatment for androgen-dependent prostate cancer in the near future.